Using Cellular Automata to Simulate Domain Evolution in Proteins - Xiao, Xuan; Xue, Guang-Fu; Stamatovic, Biljana; Qiu, Wang-Ren (Frontiers in Genetics, 2020)
Proteins have primary roles in important biological process such as catalysis, physiological function, and immune system function. Thus, the research of how proteins evolution has been a nuclear question in the field of evolutionary biology. General protein evolution models help determine the baseline expectations for evolution of sequences, and these models have extensively useful in sequence analysis and for the computer simulation of artificial sequence data sets. We have developed a new method of simulating multi-domain protein evolution, including fusions of domains, insertion and internal repetitions. It has been observed via the simulation test that the success rates achieved by the proposed predictor are remarkably high. For the convenience of the most experimental scientists, a user-friendly web-server has been established at http://jci-bioinfo.cn/domainevo, by which users can easily get their desired results without the need to go through the detailed mathematics.